The impact of rapid land use changes upon sediment yields from agricultural catchments in northern Lao PDR - Sengtaheuanghoung, Oloth; Valentin, Christian; Ribolzi, Olivier; Rouw, Anneke de; Thiebaux, Jean-Pierre (2007)
To provide data that are lacking at the catchment scale, outflow and sediment yield have Been monitored from 8 small (0.5-64 ha) rural catchments since 2001 in northern Lao PDR. Soil conservation strategies have been developed and tested on three of these catchments. Results clearly show that sediment yields can be reduced from 5-11 Mg ha-1 yr-1 under the current slash and burn system to nearly nil when appropriate practices are selected. These include improved fallow systems based on legumes. These innovative practices rehabilitate degraded land and enhance water quality.